Spatiotemporal variability of turbidity water in tidal areas of Perak River, Malaysia, based on field survey and Sentinel-2 image analysis - Takahashi Haruna; Yamasaki Yosei; Nakata Akane; Okada Shoji (E3S Web of Conferences)
In the Perak River, which flows into Malaysia, a tidal zone extends approximately 40 km from the mouth of the river, and turbid water is always present. Therefore, a detailed field survey is necessary to reveal the dynamical phenomenon of turbid water associated with the tidal zone. However, it is efficient to specify the survey area and conditions by clarifying the rough spatiotemporal variability characteristics in advance. In this study, water sampling and turbidity measurements were conducted in the tidal sensitive area of the Perak River during the satellite Sentinel-2 transit. An equation to estimate turbidity from surface reflectance at near-infrared wavelengths was experimentally developed using fine sand collected from the Perak River, and this equation was applied to past Sentinel-2 images to clarify the spatiotemporal variability characteristics of turbidity in the tidal zone. The results showed a large longitudinal variation in turbidity in the 20 km section from the mouth of the river, and a convergence zone of suspended sediment was identified when turbidity was relatively high.